2020
DOI: 10.1111/resp.13947
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and long‐term survival of patients with chronic thromboembolic pulmonary hypertension in China

Abstract: This is the first multicentre prospective registry reporting baseline characteristics and estimated survival of patients with chronic thromboembolic pulmonary hypertension (CTEPH) in China. A total of 593 patients with CTEPH were included. The long‐term survival rates are similar to those of patients in the international and Spanish registries. Pulmonary endarterectomy is an independent predictor of survival.See related Editorial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Particularly, it is difficult for us to determine whether the patients had a prior history of VTE. However, this would be less likely to bias our findings considering that the prevalence of a prior history of VTE in this study is comparable to that in previous publications (1,31). Second, the sample size of patients without a prior history of VTE was relatively small.…”
Section: Discussionmentioning
confidence: 54%
“…Particularly, it is difficult for us to determine whether the patients had a prior history of VTE. However, this would be less likely to bias our findings considering that the prevalence of a prior history of VTE in this study is comparable to that in previous publications (1,31). Second, the sample size of patients without a prior history of VTE was relatively small.…”
Section: Discussionmentioning
confidence: 54%
“…However, why only a minority of patients (cumulative incidence 0.1–9.1%) may develop PH after an initial episode of PE remains to be clarified [ 13 , 14 , 15 , 16 ]. Some epidemiological studies have identified some predisposing factors offering some insight as to the etiology of CTEPH [ 17 , 18 , 19 ]. Based on available data, it can be stated that CTEPH originates from a remodeling process of the vessel wall after embolic obstruction and is initiated and enhanced by the combination of impaired angiogenesis, reduced fibrinolysis, and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the patients in the HOPE registry are women and a history of PE/VTE is obvious in half of the patients, in concordance with the recently published data on the International CTEPH Registry [10], where the median age was 62 years for women and 63 for men and an episode of VTE was present in more than 70% of the enrolled patients. The Japanese registry [11] revealed 50.4% and 37.2% of patients had a history of deep vein thrombosis and acute pulmonary embolism, respectively. The corresponding percentages were 56.1% and 74.8% in the large European database [12] and in concordance with this registry, a large proportion of our patients had a history of PE (49%)) and DVT (30.6%) and a significant number had a history of splenectomy, perhaps due to the high prevalence of haemoglobinopathies in Greece.…”
Section: Discussionmentioning
confidence: 99%